EU AGENCIES PROCEDURE – IS THERE A POSSIBILITY FOR AN INTER-AGENCY AND CROSSSECTORAL APPROACH IN MATTERS OF SECURITY - Duić, Dunja (EU and comparative law issues and challenges series (ECLIC), 2018)
The European Agenda on Security of April 2015 indicates that the Union needs a more joinedup inter-agency and cross-sectorial approach. Explicitly, it states that “given the increasing nexus between different types of security threats, policy and action on the ground must be fully coordinated among all relevant EU agencies, in the area of Justice and Home Affairs and beyond.” Furthermore, it suggests that the Union needs to bring together all internal and external dimensions of security. This paper will take a look at the new Regulation (EU) 2016/1624 on the European Border and Coast Guard (Frontex) and analyse whether there has been improvement in the possibility for an inter-agency and a cross-sectorial approach for agencies from the Area of Common Foreign and Security Policy. The paper will try to answer the question of prospect of progress in joining internal and external dimensions of security of the Union, considering the rising threat of terrorism and the continuing migration crises that have been shaking EU since the adaptation of the European Agenda on Security.